Long-term outcome and survival rate of monopolar radial head replacement - Schnetzke, Marc; Jung, Matthias; Grötzner-Schmidt, Corinna; Nolte, Anna-Katharina; Porschke, Felix; Grützner, Paul Alfred; Gühring, Thorsten; Nolte, Philip-Christian (Journal of shoulder and elbow surgery, 2021)
Background - The purposes of this study were (1) to report functional outcomes; (2) to assess complications, revisions, and survival rate; and (3) to assess differences in functional outcomes between removed and retained radial head arthroplasties (RHAs), early and delayed treatment, and type of RHA used at long-term follow-up after monopolar RHA for unreconstructible radial head fractures or their sequelae. - Methods - Seventy-eight patients (mean age, 59.2 years) who were at least 6 years postoperatively after monopolar RHA for unreconstructible RHFs or their sequelae were included. The Mayo Elbow Performance Score (MEPS); Quick Disability of the Arm, Shoulder, and Hand (QuickDASH) score; visual analog scale; postoperative satisfaction (1-6, 6 = highly unsatisfied); range of motion; complications; and revisions were assessed. Radiographic findings were reported. Kaplan-Meier survival analysis was performed. Subgroups (RHA type, early vs. delayed surgery, RHA removed vs. retained) were compared. - Results - At a median clinical follow-up of 9.5 years (range: 6.0-28.4 years), median MEPS was 80.0 (interquartile range [IQR]: 60.0-97.5), median QuickDASH was 22.0 (IQR: 4.6-42.6), median visual analog scale was 1 (IQR: 0-4), median postoperative satisfaction was 2 (IQR: 1-3), and median arc of extension/flexion was 110° (IQR: 80°-130°). Radiographic follow-up was available for 48 patients at a median of 7.0 years (range: 2.0-15.0 years). Heterotopic ossifications were seen in 14 (29.2%), moderate-to-severe capitellar osteopenia/abrasion in 3 (6.1%), moderate-to-severe ulnohumeral degeneration in 3 (6.1%), and periprosthetic radiolucencies in 17 (35.4%) patients. Twenty-nine patients (37.2%) had complications and 20 patients (25.6%) underwent RHA exchange or removal. Kaplan-Meier analysis with failure defined as RHA exchange or removal demonstrated survival of 75.1% (95% confidence interval: 63.7-83.3) at 18 years. The highest annual failure rate was observed in the first year in which the RHAs of 7 patients (9%) were exchanged or removed. No significant differences were detected between type of RHA in MEPS (Mathys: 82.5 [75.0-100] vs. Evolve: 80.0 [60.0-95.0]; P = .341) and QuickDASH (Mathys: 12.5 [0-34.4] vs. Evolve: 26.7 [6.9-46.2]; P = .112). Early surgery (≤3 weeks) yielded significantly superior MEPS (80.0 [70.0-100.0] vs. 52.5 [30.0-83.8]; P = .014) and QuickDASH (18.6 [1.5-32.6] vs. 46.2 [31.5-75.6]; P = .002) compared with delayed surgery (>3 weeks). Patients with retained RHAs had significantly better MEPS (80.0 [67.5-100] vs. 70.0 [32.5-82.5]; P = .016) and QuickDASH (18.1 [1.7-31.9] vs. 49.1 [22.1-73.8]; P = .007) compared with patients with removed RHAs. - Conclusions - Long-term outcomes for RHA are satisfactory; however, there is a high complication and revision rate, resulting in implant survival of 75.1% at 18 years with the highest annual failure rate observed in the first postoperative year.
Gesehen am 17.08.2021